2019
DOI: 10.5539/ass.v15n8p38
|View full text |Cite
|
Sign up to set email alerts
|

Education Activities to Realize Green Campus

Abstract: The application of green concepts on campus starts from the formulation of the vision and mission, ratification of policies and development processes. The main problems in the effort to realize a green campus include a lack of involvement and individual awareness of sustainability issues and campus users are unaware of the sustainability that occurs on campus. Individual awareness and involvement of staff and students are needed to create a green campus. The purpose of this study was to analyze what educationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…At the same time, domestic scholars have also conducted a series of studies on green universities. Zhu Bifeng studied the adaptability of STARS to Chinese green campus [14], and Fachrudin proposed green building standards for Chinese green campus [2].…”
Section: Methodsmentioning
confidence: 99%
“…At the same time, domestic scholars have also conducted a series of studies on green universities. Zhu Bifeng studied the adaptability of STARS to Chinese green campus [14], and Fachrudin proposed green building standards for Chinese green campus [2].…”
Section: Methodsmentioning
confidence: 99%
“…There are tremendous studies have focused on the importance of promoting environmental sustainability on college and university campuses. Fachrudin, Fachrudin, and Utami (2019) highlighted the importance of promoting green campus engagement and activities in their research. The results of a survey conducted with 400 respondents from Universitas Sumatera Utara revealed that initiatives such as seminars, campaigns, and the implementation of a paperless policy could encourage greater involvement of the campus community in green campus initiatives.…”
Section: Literature Review On Green Campus Initiativesmentioning
confidence: 99%
“…The effect of COVID-19 on the price of Somebody returned to farm but had to be quarantined for 14 days, which led restocking to be done with a delay (Fachrudin and Suhendra, 2020 (Saokaew, 2020).…”
Section: Indonesiamentioning
confidence: 99%
“…The fluctuated price led Indian exporters to seek new markets, albeit at lower prices. This movement affected Indonesia exporting shrimp to the United States and the European Union, the two main Indonesian traditional shrimp markets(Fachrudin and Suhendra, 2020). Given that, Indonesia has a very low incidence of the COVID-19 disease (WHO, 2020), the government's restrictive measures have also been low, reducing the impact of the pandemic on the economy and trade.…”
mentioning
confidence: 99%